Pengaruh Kepemimpinan Transformasional Kepala Sekolah dan Supervisi Akademik Terhadap Deep Learning Dan Karakter Siswa - Andi Nur Adna; Muh. Yunus; Andi Mulyadi Radjab (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the influence of the principal's transformational leadership and academic supervision on the quality of deep learning implementation and student character at SMAN 2 Kepulauan Selayar. The study used a quantitative explanatory approach with a causal design. The respondents were all 46 teachers of SMAN 2 Kepulauan Selayar who were selected through a saturated sampling technique. Data were collected through questionnaires, observation, and documentation, then analyzed through validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, and F-tests. The research instrument was reliable with Cronbach's Alpha values ​​of 0.856 for transformational leadership, 0.833 for academic supervision, 0.858 for deep learning implementation, and 0.792 for student character. The results showed that transformational leadership had a positive and significant effect on the quality of deep learning implementation (B = 0.367; p = 0.010), while academic supervision had no significant effect on these variables (B = 0.205; p = 0.179). Transformational leadership does not have a significant direct effect on student character (B = 0.215; p = 0.080)